Stimulated Salivary Cortisol as a Noninvasive Diagnostic Tool for Adrenal Insufficiency - Kim, Yoon Ji; Kim, Jung Hee; Hong, A Ram; Park, Kyeong Seon; Kim, Sang Wan; Shin, Chan Soo; Kim, Seong Yeon (Endocrinology and metabolism (Seoul), 2020)
Salivary cortisol is routinely used as a diagnostic test for Cushing syndrome. The diagnostic use of salivary cortisol for adrenal insufficiency (AI), however, is less established. We aimed to investigate the utility of morning basal and adrenocorticotropic hormone-stimulated salivary cortisol in diagnosing AI in Korean adults.BACKGROUNDSalivary cortisol is routinely used as a diagnostic test for Cushing syndrome. The diagnostic use of salivary cortisol for adrenal insufficiency (AI), however, is less established. We aimed to investigate the utility of morning basal and adrenocorticotropic hormone-stimulated salivary cortisol in diagnosing AI in Korean adults.We prospectively included 120 subjects (female, n=70) from Seoul National University Hospital. AI was defined as a stimulated serum cortisol level of <496.8 nmol/L during the short Synacthen test (SST). Serum and saliva samples were drawn between 8:00 AM and 10:00 AM. Salivary cortisol levels were measured using an enzyme immunoassay kit.METHODSWe prospectively included 120 subjects (female, n=70) from Seoul National University Hospital. AI was defined as a stimulated serum cortisol level of <496.8 nmol/L during the short Synacthen test (SST). Serum and saliva samples were drawn between 8:00 AM and 10:00 AM. Salivary cortisol levels were measured using an enzyme immunoassay kit.Thirty-four patients were diagnosed with AI according to the SST results. Age, sex, body mass index, serum albumin levels, and serum creatinine levels did not significantly differ between the normal and AI groups. Basal and stimulated salivary cortisol levels were positively correlated with basal (r=0.538) and stimulated serum cortisol levels (r=0.750), respectively (all P<0.001). Receiver operating characteristic curve analysis yielded a cutoff level of morning basal salivary cortisol of 3.2 nmol/L (sensitivity, 84.9%; specificity, 73.5%; area under the curve [AUC]=0.822). The optimal cutoff value of stimulated salivary cortisol was 13.2 nmol/L (sensitivity, 90.7%; specificity, 94.1%; AUC=0.959). Subjects with a stimulated salivary cortisol level above 13.2 nmol/L but a stimulated serum cortisol level below 496.8 nmol/L (n=2) had lower serum albumin levels than those showing a concordant response.RESULTSThirty-four patients were diagnosed with AI according to the SST results. Age, sex, body mass index, serum albumin levels, and serum creatinine levels did not significantly differ between the normal and AI groups. Basal and stimulated salivary cortisol levels were positively correlated with basal (r=0.538) and stimulated serum cortisol levels (r=0.750), respectively (all P<0.001). Receiver operating characteristic curve analysis yielded a cutoff level of morning basal salivary cortisol of 3.2 nmol/L (sensitivity, 84.9%; specificity, 73.5%; area under the curve [AUC]=0.822). The optimal cutoff value of stimulated salivary cortisol was 13.2 nmol/L (sensitivity, 90.7%; specificity, 94.1%; AUC=0.959). Subjects with a stimulated salivary cortisol level above 13.2 nmol/L but a stimulated serum cortisol level below 496.8 nmol/L (n=2) had lower serum albumin levels than those showing a concordant response.The diagnostic performance of stimulated salivary cortisol measurements after the SST was comparable to serum cortisol measurements for diagnosing AI.CONCLUSIONThe diagnostic performance of stimulated salivary cortisol measurements after the SST was comparable to serum cortisol measurements for diagnosing AI.